2015
DOI: 10.1093/mnras/stv516
|View full text |Cite
|
Sign up to set email alerts
|

The first ultraviolet quasar-stacked spectrum at z ≃ 2.4 from WFC3

Abstract: The ionising continuum from active galactic nuclei (AGN) is fundamental for interpreting their broad emission lines and understanding their impact on the surrounding gas. Furthermore, it provides hints on how matter accretes onto supermassive black holes. Using HST's Wide Field Camera 3 we have constructed the first stacked ultraviolet (rest-frame wavelengths 600-2500Å) spectrum of 53 luminous quasars at z 2.4, with a state-of-the-art correction for the intervening Lyman forest and Lyman continuum absorption. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
357
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(386 citation statements)
references
References 89 publications
26
357
3
Order By: Relevance
“…The physical scales locally are expected to be larger (Bentz et al 2013), which will make variability timescales longer and variability magnitudes smaller (Vanden Berk et al 2004;Schmidt et al 2012). Blackhole masses as determined from Mg  increases with luminosity (Wu et al 2015) which in turn affects the temperature of the accretion disc (Shakura & Sunyaev 1973;Pereyra et al 2006) and thereby the position of the "big blue bump" and the degree to which the continuum is well modeled by a single power law (see also Lusso et al 2015, for a discussion). As can be seen from Overplotted in dark green is the corresponding composite generated from the full sample of SDSS quasars fulfilling the selection criteria and general agreement is observed, albeit with a brighter Balmer continuum in the SDSS-constructed composite.…”
Section: Comparison To Global Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…The physical scales locally are expected to be larger (Bentz et al 2013), which will make variability timescales longer and variability magnitudes smaller (Vanden Berk et al 2004;Schmidt et al 2012). Blackhole masses as determined from Mg  increases with luminosity (Wu et al 2015) which in turn affects the temperature of the accretion disc (Shakura & Sunyaev 1973;Pereyra et al 2006) and thereby the position of the "big blue bump" and the degree to which the continuum is well modeled by a single power law (see also Lusso et al 2015, for a discussion). As can be seen from Overplotted in dark green is the corresponding composite generated from the full sample of SDSS quasars fulfilling the selection criteria and general agreement is observed, albeit with a brighter Balmer continuum in the SDSS-constructed composite.…”
Section: Comparison To Global Populationmentioning
confidence: 99%
“…The composite by Vanden Berk et al (2001) consists of 2204 SDSS quasars at z median = 1.253 with absolute M r -magnitudes between −18.0 and −26.5 and therefore intrinsically fainter and lower redshift objects. Lusso et al (2015) calculated the M i (z = 2) mag for the 184 constituent objects in Telfer et al (2002) observed with FOS, GHRS and STIS onboard the Hubble Space Telescope and find an average M i (z = 2) ∼ −27.5 at z ∼ 1.2, which yields a composite of fainter, more nearby sources. For construction of a composite, Glikman et al (2006) used 27 objects at z ∼ 0.25 with an average absolute i-band magnitude M i ∼ −24 observed with IRTF, therefore constituting a Notes.…”
Section: Comparison To Existing Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuum recovery in this region requires high-resolution UV spectra, e.g. from HST (Finn et al 2014;Lusso et al 2015).…”
Section: Data and Sed Constructionmentioning
confidence: 99%